Dexamethasone’s Clinical Efficacy in Experimental Autoimmune Pancreatitis Correlates with a Unique Transcriptomic Signature, Whilst Kinase Inhibitors Are Not Effective - Ottavia Agrifoglio; Anika Kasprick; Natalie Gross; Marc Wahlig; Emilia Kauffold; Aline Woitas; Artem Vorobyev; Luise Ehlers; Ralf J. Ludwig; Katja Bieber; Robert Jaster (Biomedicines)
(1) Background: Autoimmune pancreatitis (AIP) is mainly treated with steroids. Using an AIP mouse model, we investigated two potential alternatives, the transforming growth factor-β-activated kinase 1 inhibitor, takinib, and the Janus kinase inhibitor, tofacitinib. (2) Methods: In a multicenter preclinical study, MRL/MpJ mice were injected with polyinosinic/polycytidylic acid (poly I:C) for two weeks to induce AIP. They were then treated for four weeks with either takinib (25, 50, or 75 mg/kg body weight), tofacitinib (5, 10 or 15 mg/kg), dexamethasone (1 mg/kg), or solvent, while the poly I:C injections were continued. The severity of AIP was assessed histopathologically. Flow cytometry was used to examine lymphocyte subtypes in the spleen and mesenteric lymph nodes. The pancreatic gene expression profiles were analyzed by RNA sequencing. (3) Results: Poly I:C-treated mice developed severe AIP with inflammation, destruction of acinar tissue, and fibrosis. Dexamethasone significantly attenuated the disease, while takinib or tofacitinib had no effects. Dexamethasone also antagonized the effects of poly I:C on the relative frequencies of the AIP-associated lymphocyte subtypes CD4/CD69, CD8/CD44high, and CD4/CD25/FoxP3 in the spleen. In the principal component analysis of pancreatic transcriptomics, poly I:C-injected mice treated with tofacitinib, takinib, or solvent clustered together, while untreated and dexamethasone-treated mice formed separate, unique clusters. (4) Conclusions: Dexamethasone effectively reduced AIP severity, while takinib and tofacitinib were ineffective. The unique gene expression profile in dexamethasone-treated mice may provide a basis for identifying new drug targets for AIP treatment.